Development of Connected-Pjbl Model Book Validation Instruments - Ilwandri (Indonesia Journal of Engineering and Education Technology (IJEET), 2023)
This research is a type of development research that aims to produce valid validation instrument products for the Connected-PjBL Model book to Improve Students' 21st Century Skills in Physics Learning. This validation instrument was assessed by 2 experts. With data collection techniques in the form of validation instrument assessment sheets and data analysis techniques using the Cohen's Kappa formula. From the results of data analysis, it was obtained that the average validation value was 0.85 in the valid category. From the analysis of the data, it can be concluded that the validation instrument for the Connected-PjBL Model book to Improve Students' 21st Century Skills in Physics Learning meets the valid criteria and can be used to validate the Connected-PjBL Model book.